Factors Associated with the Incidence of Dengue Hemorrhagic Fever in the Working Area of Paal Lima Health Center, Jambi City 2024 - Siahaan, Putri Melani; Sari, Puspita; Reskiaddin, La Ode (Formosa Journal of Multidisciplinary Research, 2024)
Dengue fever is an infectious disease that continues to be a global issue. In 2021, the CFR in Jambi Province was 1.4%. Puskemas Paal V Jambi City from the data there were 36 DHF patients in 2022 making the puskesmas with the highest number of DHF cases. The aim of this research was to determine what factors are associated with the incidence of DHF in the Paal V Health Center Working Area of Jambi City. The research approach used is quantitative using a case-control research design. This study's sample approach utilized a total sample size of 72 people with a ratio of 1: 1, namely 36 cases and 36 controls.  This study's statistical test was the Chi Square test. The findings revealed a correlation between the frequency of depleting water reservoirs (P=0.004), health worker support (P=0.006), knowledge (P=0.000), attitude (P=0.003) with the incidence of DHF. There was no association between water storage cover (P=0.777), experience of counseling with DHF incidence (P=0.057). The frequency of draining water reservoirs, support from health workers, knowledge and attitudes can increase the risk of DHF cases, so it is necessary to increase education for the entire community.